Formulation of Investigation of Criminal Acts of Theft with Justice-Based Aggravation (Case Study of Nabire Police Resort) - Anugerah, Muhammad Dito; Laksana, Andri Winjaya (UNISSULA Semarang, 2025)
Indonesia is a unitary state in the form of a republic. This statement is clearly stated in Article 1 Paragraph 3 of the Fourth Amendment to the 1945 Constitution of the Republic of Indonesia, which states that Indonesia is a country of law. Based on the supremacy of law, it states that